Observed damage in public school buildings during the 2017 Mexico earthquakes. Issue 2 (December 2020) - Alcocer, Sergio M; Murià-Vila, David; Fernández-Sola, Luciano R; Ordaz, Mario; Arce, José C
In September 2017, two major earthquakes struck south and central Mexico. These earthquakes produced widespread damage in public and private school infrastructure. In Mexico, all school buildings are classified as essential infrastructure and are expected to attain an immediate occupancy performance level after major earthquakes. However, there is a large variation in the quality of the design and construction practices of these buildings due to age of construction, material quality and availability, and great socioeconomic gaps around the country. In this article, an analysis of the observed damage in public school buildings is presented. The results are analyzed depending on the structural system, construction material, and year of construction. The results showed that damage intensity in seismically designed buildings was significantly lower than that observed in the pre-1985 structures. Load bearing and infill masonry walls were the most damaged structural elements.